Women's Prostration in Prayer: Qur'anic Interpretation, Worship Ethics, and Contemporary Challenges - Nilna Fauza (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This article examines the practice of women’s prostration (sujud) in prayer by integrating Qur’anic interpretation and the ethics of worship. Contemporary Muslim communities often experience differences in the posture of women’s sujud, which are frequently judged normatively as right or wrong, while the spiritual meaning of prostration as total submission to God is neglected. The study addresses the question: how does the Qur’an conceptualize sujud as spiritual surrender, and how can this meaning function as an ethical framework for understanding diverse women’s practices? Methods: This research employs a qualitative library method with a thematic (maudhu‘i) Qur’anic interpretation combined with analysis of fiqh and socio-religious practices. Key Findings: The findings show that sujud in the Qur’an represents a multidimensional submission—physical, psychological, and ontological—while juristic variations in women’s posture reflect ethical considerations of modesty rather than inequality. Misunderstanding arises from a technical-legal approach detached from spiritual awareness and amplified by imitative practices in the digital era. Contribution: The study contributes theoretically by proposing an integrative model of tafsir, fiqh, and spiritual ethics, and practically by offering a reflective framework for teaching prayer that reduces conflict and strengthens religious consciousness. Conclusion: In conclusion, differences in women’s sujud should be understood as legitimate ijtihad within the shared goal of humility before God, transforming ritual from mechanical movement into meaningful devotion.